Molecular Electronics: Advances in Synthesis and Measurement of Charge Transport in DNA‐Based Derivatives (Adv. Mater. 41/2018). Issue 41 (8th October 2018) - Zhuravel, Roman; Stern, Avigail; Fardian‐Melamed, Natalie; Eidelshtein, Gennady; Katrivas, Liat; Rotem, Dvir; Kotlyar, Alexander B.; Porath, Danny
Abstract : Charge transport through molecular structures is interesting both scientifically and technologically and, to date, DNA is the only type of polymer that can transport significant currents over distances of more than a few nanometers in individual molecules. In article number1706984, Alexander B. Kotlyar, Danny Porath, and co‐workers survey the synthesis, electrical characterization, and theoretical models of several unique DNA derivatives, which are generally more promising than native DNA due to their improved charge‐transport properties.